The Determinants Of Inward Foreign Direct Investment In Business Services Across European Regions - Valentina Meliciani; Davide Castellani; Loredana Mirra (European Regional Science Association (ERSA), 2013)
The paper accounts for the determinants of inward foreign direct investment in business services across the EU-27 regions. Together with the traditional variables considered in the literature (market size, market quality, agglomeration economies, labour cost, technology, human capital), we focus on the role of forward linkages with manufacturing sectors and other service sectors as attractors of business services FDI at the regional level. This hypothesis is based on the evidence that the growth of business services is mostly due to increasing intermediate demand by other services industries and by manufacturing industries and on the importance of geographical proximity for forward linkages in services. To our knowledge, there are no studies investigating the role of forward linkages for the location of FDI. This paper aims therefore to fill this gap and add to the FDI literature by providing a picture of the specificities of the determinants of FDI in business services at the regional level. The empirical analysis draws upon the database fDi Markets, from which we selected projects having as a destination NUTS 2 European regions in the sectors of Business services over the period 2003-2008. Data on FDI have been matched with data drawn from the Eurostat Regio database. Forward linkages have been constructed using the OECD Input/Output database. By estimating a negative binomial model, we find that regions specialised in those (manufacturing) sectors that are high potential users of business services attract more FDI than other regions. This confirms the role of geographical proximity for forward linkages in services and shows the role played by the existing structure of domestic production for the localisation of business service FDI, particularly in the case of manufacturing.
Keywords: R12; L80; F23; 330; FDI; Business Services; Regional Specialisation; Forward linkages